An introduction to teaching : psychological perspectives (Oxford, UK ; Cambridge, Mass. : Blackwell, 1995)
Basic processes. Contexts for learning. Teaching and classroom management. Assessment and evaluation.
Keywords: Education; Teaching; Educational psychology; Learning, Psychology of; Educational psychology; Teaching -- Psychological aspects